Climate change and its effects on irrigated rice yield in the state of Rio Grande do Sul, Brazil - Walter, Lidiane Cristine; Streck, Nereu Augusto; Rosa, Hamilton Telles; Ferraz, Simone Erotildes Teleginski; Cera, Jossana Ceolin (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to estimate the irrigated rice grain yield in the rice production regions of the state of Rio Grande do Sul, Brazil, in different sowing dates, in a future climatic scenario – the A1B scenario from the Intergovernmental Panel on Climate Change (IPCC) – and to determine possible changes in the current sowing calendar for irrigated rice in this scenario. The SimulArroz model was used, considering three maturity groups (early, middle, and late) and seven sowing dates (8/1, 9/1, 10/1, 11/1, 12/1, 1/1, and 1/2) for each year of the climatic scenario, in the six rice production regions of the state. Among the rice production regions, there is a variation in the effect of climate change on yield, in which the Fronteira Oeste region is less favored and the Zona Sul region more favored in the future scenario. The projected climate change has a positive effect on rice grain yield in the state of Rio Grande do Sul, Brazil, mainly at the end of the 21st century, when the sowing period may be anticipated.